2009
DOI: 10.1038/ncb1880
|View full text |Cite
|
Sign up to set email alerts
|

The Patched dependence receptor triggers apoptosis through a DRAL–caspase-9 complex

Abstract: Sonic hedgehog (Shh) and its main receptor Patched (Ptc) are implicated in both neural development and tumorigenesis1, 2. Beside the classic morphogen activity of Shh, Shh is also a survival factor3, 4. Along this line, Ptc has been shown to function as a dependence receptor, inducing apoptosis in the absence of Shh, while its pro-apoptotic activity is blocked in Shh presence5. Here we show that, in the absence of its ligand, Ptc interacts with the adaptor protein DRAL/FHL2. DRAL/FHL2 is required for the pro-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 31 publications
5
118
1
1
Order By: Relevance
“…The SHH receptor Patched was later shown to have an intrinsic pro-apoptotic activity both in vitro and in the chick neural tube, which could be rescued by SHH stimulation, consistent with a dependence receptor activity (Thibert et al 2003). More recently, the signaling pathway underlying Patched-mediated apoptosis was shown to involve direct interaction with a proapoptotic complex comprising caspase 9 and the adaptor protein DRAL (Mille et al 2009). As SHH and Netrins both have attractant effects on commissural neurons, it will be interesting to test how each cue interacts with the other to coordinate, not only the navigation, but also the survival of similar neuronal populations.…”
Section: Other Guidance Moleculesmentioning
confidence: 89%
“…The SHH receptor Patched was later shown to have an intrinsic pro-apoptotic activity both in vitro and in the chick neural tube, which could be rescued by SHH stimulation, consistent with a dependence receptor activity (Thibert et al 2003). More recently, the signaling pathway underlying Patched-mediated apoptosis was shown to involve direct interaction with a proapoptotic complex comprising caspase 9 and the adaptor protein DRAL (Mille et al 2009). As SHH and Netrins both have attractant effects on commissural neurons, it will be interesting to test how each cue interacts with the other to coordinate, not only the navigation, but also the survival of similar neuronal populations.…”
Section: Other Guidance Moleculesmentioning
confidence: 89%
“…Ptc was indeed found to interact through its ADD, and only in the absence of its ligand Shh, with DRAL/FHL2 (Mille et al, 2009b). DRAL was already known to promote apoptosis through an unknown mechanism in a wide variety of cells when overexpressed (Scholl et al, 2000) and to interact with TUCAN, a CARD-containing adaptor protein for caspases 1 and 9 (Stilo et al, 2002).…”
Section: Proapoptotic Signaling By Drsmentioning
confidence: 99%
“…Interestingly, it was demonstrated that Shh functions as a survival factor by inhibiting the apoptotic function of Ptc and that this proapoptotic function is crucial for adequate neural tube development (Thibert et al, 2003;Mille et al, 2009b).…”
Section: Role Of Drs During Embryonic Developmentmentioning
confidence: 99%
“…Thus, in the absence of their ligands, some dependence receptors like Patched and DCC appear to interact with the cytoplasmic adaptor protein DRAL to assemble a caspase-9-activating platform. 55 Another dependence receptor, UNC5B, responds to the withdrawal of netrin-1 by recruiting a signaling complex that includes protein phosphatase 2A (PP2A) and death-associated protein kinase 1 (DAPK1). 56 This multiprotein interaction would lead to the PP2A-mediated dephosphorylation of DAPK, in turn unleashing its multifaceted pro-apoptotic potential.…”
Section: Definition Of 'Extrinsic Apoptosis'mentioning
confidence: 99%